(untitled) (Journal of Pakistan Orthopaedic Association, 2018)
ABSTRACT Objective: To determine the radiological outcome of cannulated hip screws fixation in nondisplaced femoral neck fractures. Methods: This is a cross sectional study conducted between March 2011 to March 2016 at Orthopedic Surgery Department, Liaquat National Hospital, Karachi. Total 251 patients with nondisplaced femur neck fracture with Garden variety classification type I & II were indulged. All patients underwent cannulated screws fixation. Post-operative hip radiographs and MRI were analyzed for non-union and avascular necrosis. Calculation of descriptive statistics performed. Chi-square test was applied. Results: Study comprises 106 males and 56 females. Mean age was 37.98±8.02 years. Mean span of fracture 3.64±1.59 days. Mean hospital stay was 8.49±0.87 days. Nonunion was observed in 12.4% patients and avascular necrosis was observed in 6.0% cases. Significant association of non-union was observed with age and duration of fracture. While avascular necrosis was observed with hospital stay. Conclusion: Neck of femur fracture fixation through cannulated hip screws remains a valid option with postoperative complications less than 15%.